Konsep Kedewasaan Subyek Hukum - Sainul, Ahmad (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2019)
There is a difference in the concept of the legal maturity limit according to Islamic law and positive law. The legal subject's maturity is fifteen years old or ihtilam for men and menstruation for women. whereas according to positive law there is no legal certainty regarding legal skills in the age of 18 years, 21 years, or after marriage, resulting in confusion in determining one's skills before the law. Then the age difference in the Marriage Law for men and women needs to be equalized and needs to be re-agreed in accordance with physical and mental considerations for all parties who will get married